2006
DOI: 10.2746/042516406775374351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local analgesia on movement of the equine back

Abstract: Summary Reasons for performing study: Diagnostic infiltration of local anaesthetic solution is commonly used in cases of equine back pain. Evaluation is subjective and it is not known how local analgesia of the back affects horses without clinical signs of back pain. Objectives: To evaluate the effect of infiltration of local anaesthetics on the movement of the back in horses without clinical signs of back pain, and to evaluate the usefulness of kinematic studies as an objective and quantitative tool in eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…This has been used extensively to determine back kinematics in ridden and unridden subjects at various gaits [27][28][29][30][31][32][33][34][35][36][37][38][39] and does not need laboratory conditions. The aim of the study was to investigate the relationship between subjective grading of muscle development (the "muscle score") and back kinematics.…”
Section: Muscle Tensionmentioning
confidence: 99%
“…This has been used extensively to determine back kinematics in ridden and unridden subjects at various gaits [27][28][29][30][31][32][33][34][35][36][37][38][39] and does not need laboratory conditions. The aim of the study was to investigate the relationship between subjective grading of muscle development (the "muscle score") and back kinematics.…”
Section: Muscle Tensionmentioning
confidence: 99%
“…However, Holm et al . () found that local infiltration of an anaesthetic solution in and around T16 to L2 results in a change in the function of the back in asymptomatic horses. Horses without perceived back pain showed increases in dorsoventral flexibility as well as lateral bending following infusion of mepivicaine along the spine.…”
Section: Infiltration Of Local Anaesthesia As An Aid To Diagnosismentioning
confidence: 98%
“…Une augmentation de la perception de la douleur avec le temps et la répétition des stimulus nociceptifs (wind up) (Rang et al 1995) et une adaptation des mouvements à la douleur chronique (Wennerstrand et al 2004 ;Bromily, 2009) pourraient empê-cher une normalisation immédiate des mouvements après l'anesthésie. Par ailleurs, l'aanesthésie semble affecter le mouvement du dos chez des animaux sains (Holm et al 2006).…”
Section: Figure 3 : Illustration Des Observations De La Locomotion Suunclassified